2019
DOI: 10.25207/1608-6228-2019-26-6-18-27
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Functional Varieties of Labial Frenum in Children During the Mixed Dentition Period

Abstract: Aim. To study the anatomical and functional varieties of labial frenum and their prevalence in children aged 6–11 years in the territories of the Krasnodar Krai.Materials and methods. We have studied the prevalence of varieties of labial frenum anomalies in 120 children at the initial and fi nal periods of mixed dentition. A preventive examination of 60 children (1st observation group) and 60 children receiving orthodontic treatment (2nd observation group) at the children’s dental department of the Dental Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Similar conclusions were made by researchers from the Institute of Orthopedics and Dentistry in Japan, who found that the effect on posture can have a significant impact on the results of orthodontic treatment. Based on the work of Ayupova et al, [ 2 ] an integrated approach to the treatment of patients with bite deformities and posture problems is indeed the most effective and provides the best long-term results.…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions were made by researchers from the Institute of Orthopedics and Dentistry in Japan, who found that the effect on posture can have a significant impact on the results of orthodontic treatment. Based on the work of Ayupova et al, [ 2 ] an integrated approach to the treatment of patients with bite deformities and posture problems is indeed the most effective and provides the best long-term results.…”
Section: Introductionmentioning
confidence: 99%